2020
DOI: 10.21203/rs.3.rs-87486/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Earliest Detection to Date of SARS-CoV-2 in Florida: Identification Together With Influenza Virus on the Main Entry Door of a University Building, February 2020

Abstract: BackgroundQuestions persist about patterns of initial dissemination of SARS-CoV-2 in the United States in early 2020.MethodsIn February and March, 2020, environmental surface swab samples were collected from the handle of the main entry door of a major university building in Florida, as part of a pilot surveillance project screening for influenza. Samples were taken at the end of regular classroom hours, between the dates of February 1-5 and February 19-March 4, 2020. ResultsInfluenza H1N1pdm09 was isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…from the NP swab to confirm the 12-nt deletion. Phylogenetic analyses performed as previously described (2) revealed that UF-8 was closely related to early SARS-CoV-2 strains that circulated locally, but we did not see evidence of dissemination based on sequence analyses of subsequent strains from our institution (Fig. 1a).…”
mentioning
confidence: 65%
“…from the NP swab to confirm the 12-nt deletion. Phylogenetic analyses performed as previously described (2) revealed that UF-8 was closely related to early SARS-CoV-2 strains that circulated locally, but we did not see evidence of dissemination based on sequence analyses of subsequent strains from our institution (Fig. 1a).…”
mentioning
confidence: 65%
“…The systematic review included 37 eligible studies and the authors reported that contamination of the surfaces with SARS-CoV-2 RNA was detected on a wide range of surfaces with the highest contamination rates were detected in healthcare facilities where 17.7% and 10.1% of the samples that were taken from hospital settings and non-hospital settings were positive, respectively. Furthermore, in their systematic review, they found that only six [22,24,[26][27][28][29] out of the 37 eligible studies have tested the viability/infectivity of the detected SARS-CoV-2 RNA from 242 positive surface samples but the viral viability was not confirmed. Although studies of SARS-CoV-2 viability on surfaces are scarce, surface transmission may be possible [30].…”
Section: Discussionmentioning
confidence: 99%
“…Phylodynamic tools, such as NextStrain [6] and BEAST [23,1], are now routinely utilized to monitor evolution and population dynamics of epidemics based on real-time deposition of pathogen sequences in databases (e.g. Gen-Bank, HIVdatabases, GISAID) [22,14,12,10,15,13,24]. Not unlike traditional epidemiological analysis, however, these methods can significantly be affected by sampling bias [7], and sampling during outbreaks are rarely performed randomly from a representative, stratified population [21].…”
Section: Introductionmentioning
confidence: 99%